A user-driven association rule mining based on templates for multi-relational data - Valêncio, Carlos Roberto [UNESP]; Morais, Guilherme Henrique [UNESP]; Fortes, Márcio Zamboti; Colombini, Angelo Cesar; Neves, Leandro Alves [UNESP]; Tronco, Mario Luiz; Tenório, William [UNESP] (Science Publications, 2018)
Data mining algorithms to find association rules are an important tool to extract knowledge from databases. However, these algorithms produce an enormous amount of rules, many of which could be redundant or irrelevant for a specific decision-making process. Also, the use of previous knowledge and hypothesis are not considered by these algorithms. On the other hand, most existing data mining approaches look for patterns in a single data table, ignoring the relations presented in relational databases. The contribution of this paper is the proposition of a multirelational data mining algorithm based on association rules, called TBMRRadix, which considers previous knowledge and hypothesis through the using of the Templates technique. Applying this approach over two real databases, we were able to reduce the number of generated rules, use the existing knowledge about the data and reduce the waste of computational resources while processing. Our experiments show that the developed algorithm was also able to perform in a multi-relational environment, while the MR-Radix, that does not use Templates technique, was not.
Keywords: Association rules; Data mining; Knowledge discovery in databases; Multi-relational data mining; Templates; User-driven filter